168k views
4 votes
-8 + 10 + (-3) -(-2)

User Belterius
by
5.0k points

2 Answers

6 votes

Answer:

1

Explanation:


-8+10+\left(-3\right)-\left(-2\right)\\\\Follow\:the\:PEMDAS\:order\:of\:operations\\\\\mathrm{Add\:and\:subtract\:\left(left\:to\:right\right)}\:\:\\\\-8+10=2\\\\=2+\left(-3\right)-\left(-2\right)\\\\\mathrm{Apply\:rule\:}+\left(-a\right)\:=\:-a\\\\+\left(-3\right)=-3\\\\=2-3-\left(-2\right)\\\\2-3=-1\\\\=-1-\left(-2\right)\\\\=-1+2\\\\=1

User JSantos
by
5.0k points
1 vote

Answer:

1

Explanation:

-8 + 10 + (-3) - (-2)

=> -8 + 10 - 3 + 2

=> 12 - 11

=> 1

User Ali Kianoor
by
4.7k points